Root-cause Analysis of Mortality After Pancreatic Resection (CARE Study): A Multicenter Cohort Study. Issue 5 (29th November 2021) - Beugniez, César; Sauvanet, Alain; Sulpice, Laurent; Gaujoux, Sébastien; Turrini, Olivier; Truant, Stéphanie; Schwarz, Lilian; Piessen, Guillaume; Regimbeau, Jean Marc; Muscari, Fabrice; Adham, Mustapha; Pattou, François; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Analyze a multicenter cohort of deceased patients after pancreatectomy in high-volume centers in France by performing a root-cause analysis (RCA) to define the avoidable mortality rate. Background: Despite undeniable progress in pancreatic surgery for over a century, postoperative outcome remains particularly worse and could be further improved. Methods: All patients undergoing pancreatectomy between January 2015 and December 2018 and died postoperatively within 90 days after were included. RCA was performed in 2 stages: the first being the exhaustive collection of data concerning each patient from preoperative to death and the second being blind analysis of files by an independent expert committee. A typical root cause of death was defined with the identification of avoidable death. Results: Among the 3195 patients operated on in 9 participating centers, 140 (4.4%) died within 90 days after surgery. After the exclusion of 39 patients, 101 patients were analyzed. The cause of death was identified in 90% of cases. After RCA, mortality was preventable in 30% of cases, mostly consequently to a preoperative assessment (disease evaluation) or a deficient postoperative management (notably pancreatic fistula and hemorrhage). An inappropriate intraoperative decision was incriminated in 10% of cases. The comparative analysis showed that young age and arterial resection, especially unplanned, were often associated with avoidable mortality. Conclusions: One-third of postoperative mortality after pancreatectomy seems to be avoidable, even if the surgery is performed in high volume centers. These data suggest that improving postoperative pancreatectomy outcome requires a multidisciplinary, rigorous, and personalized management.